Identification of novel antiacetylated vimentin antibodies in patients with early inflammatory arthritis. Issue 6 (9th July 2015) - Juarez, Maria; Bang, Holger; Hammar, Friederike; Reimer, Ulf; Dyke, Bernard; Sahbudin, Ilfita; Buckley, Christopher D; Fisher, Benjamin; Filer, Andrew; Raza, Karim
Abstract : Objective: To investigate serum antibody reactivity against a panel of post-translationally modified vimentin peptides (PTMPs) in patients with early inflammatory arthritis. Methods: A panel of PTMPs was developed. Microtitre plates were coated with peptides derived from vimentin that were identical in length and composition except at one amino acid that was changed to introduce one of three post-translational modifications (PTMs)—either a citrullinated, carbamylated or acetylated residue. Sera of 268 treatment-naive patients with early inflammatory arthritis and symptoms ≤3 months' duration were tested. Patients were assigned to one of three outcome categories at 18-month follow-up (rheumatoid arthritis (RA), persistent non-RA arthritis and resolving arthritis). Results: Antibodies against citrullinated, carbamylated and acetylated vimentin peptides were detected in the sera of patients with early inflammatory arthritis. The proportion of patients seropositive for all antibody types was significantly higher in the RA group than in the other groups. Anti cyclic citrullinated peptide (CCP)-positive patients with RA had higher numbers of peptides recognised and higher levels of antibodies against those peptides, representing a distinct profile compared with the other groups. Conclusions: We show for the first time that antibodies against acetylated vimentin are present in the sera of patients with early RA and confirm and extend previous observations regarding anticitrullinated and anticarbamylated antibodies.